Zaman klasik di Nusantara tumpuan kajian di Sumatera - Budi Utomo, Bambang; Hassan Shuhaimi bin Nik Abd. Rahman Nik. (Kuala Lumpur Dewan Bahasa dan Pustaka, 2008)
History and antiquity of Sumatera.
Includes bibliographical references (pages 685-701) and index.
In Malay.
Keywords: Sumatra (Indonesia) -- Antiquities; Sumatra (Indonesia) -- Civilization; Sumatra (Indonesia) -- History